Employee self-efficacy and strategic human resources management - AFOUDA , Codjo Sabin (Revue Internationale des Sciences de Gestion, 2025)
Research into strategic human resource management has been in progress for some thirty years. Several approaches have been developed, including universalist, contingency and configurational approaches. Recently, there has also been an evolution in SHRM towards taking into account the psychological capital of employees. However, the literature on this subject has only touched on it briefly. As a result, there are many unexplained factors. This article provides a structured literature review on strategic human resources management with a focus on psychological capital, particularly self-efficacy, as a lever for organizational performance. It develops an explanatory conceptual framework linking HR development practices (training, mentoring, coaching) to the different dimensions of self-efficacy (cognitive, motivational, emotional, selection processes), leading to research proposals and an integrative conceptual model.